2012
DOI: 10.1590/s0101-20612012005000028
|View full text |Cite
|
Sign up to set email alerts
|

Integration of cooking and vacuum cooling of carrots in a same vessel

Abstract: Cooked vegetables are commonly used in the preparation of ready-to-eat foods. The integration of cooking and cooling of carrots and vacuum cooling in a single vessel is described in this paper. The combination of different methods of cooking and vacuum cooling was investigated. Integrated processes of cooking and vacuum cooling in a same vessel enabled obtaining cooked and cooled carrots at the final temperature of 10 ºC, which is adequate for preparing ready-to-eat foods safely. When cooking and cooling steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In relation to hygienic compliance, in the first application of the checklist most of the food and beverage areas of hotels were classified in Group 3 (Table 2), with mean and standard deviation of 12% AE 2 of compliance. Other studies conducted in Brazil have also found low percentages of compliance in the hygienic evaluation of foodservices (Cortese, Veiros, Feldman, & Cavalli, 2016;de Almeida, André, Campos, & Díaz, 2014;Lockis et al, 2011;Rodrigues, Silva, & Aleixo, 2012;Stangarlin et al, 2013), which reveals that despite the mandatory requiring the implementation of the good handling practices in foodservices in the country for more than one decade, there are still challenges to be overcome.…”
Section: % Adequacymentioning
confidence: 96%
“…In relation to hygienic compliance, in the first application of the checklist most of the food and beverage areas of hotels were classified in Group 3 (Table 2), with mean and standard deviation of 12% AE 2 of compliance. Other studies conducted in Brazil have also found low percentages of compliance in the hygienic evaluation of foodservices (Cortese, Veiros, Feldman, & Cavalli, 2016;de Almeida, André, Campos, & Díaz, 2014;Lockis et al, 2011;Rodrigues, Silva, & Aleixo, 2012;Stangarlin et al, 2013), which reveals that despite the mandatory requiring the implementation of the good handling practices in foodservices in the country for more than one decade, there are still challenges to be overcome.…”
Section: % Adequacymentioning
confidence: 96%
“…Several methods have been attempted to overcome this problem especially for meat products. These include pre-wetting prior to vacuum cooling (McDonald and Sun, 2000); brine solution injection (Desmond et al, 2002); vacuum cooling of small meat pieces in soup (Houska et al, 2003); pulsed immersion vacuum cooling (Cheng and Sun, 2006); combined vacuum cooling and air blast cooling (Jackman et al, 2007); integration of cooking and vacuum cooling (Rodrigues et al, 2012;Schmidt et al, 2010;Schmidt and Laurindo, 2014); vacuum cooling followed by immersion vacuum cooling (Dong et al, 2012); immersion vacuum cooling of large meat products (Feng et al, 2013); pressure control Song and Liu, 2014). Of these methods, immersion vacuum cooling can drastically reduce moisture loss rate (Feng et al, 2012), because most of water used to refrigerate comes from the surrounding hot soup or cold water.…”
Section: Introductionmentioning
confidence: 99%
“…When the vacuum precooling starts, with the effect of pressure, the water available in the interior of the product migrates to the surface of the product through boiling and evaporates. Therefore, cooling time becomes considerably shorter (Houska et al, 2003;, 2001aMcDonald et al, , 2001McDonald et al, , 2002Wang & Sun, 2001, 2002a, b, 2004Rodrigues et al, 2012). The aims of the present study were: I) to treat cauliflower with forced air, hydro and vacuum precooling processes; II) to measure operating parameters such as temperature decrease, weight loss, energy consumption, and vacuum values during precooling; III) to model time-dependent temperature; IV) to determine the statistical differences between the values measured and the predicted values using the model; and V) to determine hardness and colour parameters after precooling.…”
Section: Introductionmentioning
confidence: 99%